PENGARUH PENGETAHUAN MAHASISWA TENTANG RIBA & BAGI HASIL TERHADAP MINAT MENABUNG DI BANK SYARIAH - Khofifah Khofifah; Dwiyani Sudaryanti; Harun Alrasyid (El-Aswaq: Islamic Economics and Finance Journal, 2022)
Sharia Bank is a banking institution that operates its business with sharia principles. There is a fundamental difference between Islamic banks and conventional banks, namely Islamic banks do not use the interest system (usury) in every transaction, besides that Islamic banks also use a profit-sharing system in profit sharing. However, there are still many who do not know about this, this can be seen from the results of the Islamic financial literacy index in 2019 which shows that public literacy regarding Islamic finance is still low, with a value of only 8.93%, meaning that out of 100 people only 8 people are eligible. know about Islamic finance. Therefore, this study aims to determine the effect of knowledge about usury and profit sharing on interest in saving in Islamic banks. This research uses a questionnaire method and is a quantitative research. The population in this study were students of the Islamic University of Malang. From the results of the study, it is known that knowledge of usury & profit sharing has a positive and significant effect on interest in saving in Islamic banks.